KONTRIBUSI BEA CUKAI TERHADAP PERTUMBUHAN EKONOMI REGIONAL KHUSUSNYA DI KABUPATEN ACEH BARAT - Syahril Syahril; Helmi Noviar; Damrus Damrus; Alfian Anas; Yunidar Purnama Sari (Universitas Teuku Umar, 2022)
Economic activity that has a role as a driving force for the economy of a region or country is trade, namely through export and import activities. Both of these activities contribute to regional or state revenues, so supervision and management are needed to optimize these activities, namely through Customs and Excise. The existence of Customs in each region can be a forum for exporters and importers to increase their productivity, so that this trade process will run smoothly and in the end can contribute to regional economic growth in each region, especially in West Aceh Regency. keywords: Customs and Excises, Economic Growth, Export, Import.